2016
DOI: 10.21608/jbaar.2016.108934
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of heavy metals in freshwater snails in relation to lining of water courses in Egypt.

Abstract: The present study was aimed to determine the heavy metal concentrations in whole body of fresh water snails in relation to lining of water courses in two governorates (Behaira (Nubaria) and Giza) Through four successive seasons from Septemper 2013, to October 2014. The obtained results indicated that the electrical conductivity (EC) and iron metal (Fe) showed the highest values and generally the physicochemical measurements indicated that no significant difference between the two tested habitats, however, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The bioaccumulation of Mn heavy metal in H. duryi tissue was higher than that in tissues of P. acuta and B. alexandrina snails. These results were in good accordance with Abdel Kader et al ( 2016 ) who found that P. acuta and H. duryi were the highest snails that could accumulate heavy metals in their tissue and reasoned the high variation in BAF values depended on the type of the snail and the metal. The present results showed that BAF is higher than one in the three snails type and this indicated that these snails were tolerant (Liao et al 2003 ; Ávila et al 2017 ; Kachenga et al 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The bioaccumulation of Mn heavy metal in H. duryi tissue was higher than that in tissues of P. acuta and B. alexandrina snails. These results were in good accordance with Abdel Kader et al ( 2016 ) who found that P. acuta and H. duryi were the highest snails that could accumulate heavy metals in their tissue and reasoned the high variation in BAF values depended on the type of the snail and the metal. The present results showed that BAF is higher than one in the three snails type and this indicated that these snails were tolerant (Liao et al 2003 ; Ávila et al 2017 ; Kachenga et al 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Determination of heavy metals in water samples and snail’s tissues was performed by using atomic absorption spectrophotometry (AAS) in Environmental Research Laboratory, Theodor Bilharz Research Institute (TBRI), according to the method of Abdel Kader et al ( 2016 ). Analysis of heavy metals in water: For the analysis of total heavy metals, water samples (200 ml) were digested with 5 ml of acidified concentrated nitric acid (HNO3) on a hot plate and filtered by Whatman No.…”
Section: Methodsmentioning
confidence: 99%
“…Water samples (200ml) were digested with 5ml of di-acid mixture (9 HNO 3 : 4 HCIO 4 ) on a hot plate and filtered by Whatman No. 42 filter paper, and double distilled water was added to bring the volume up to 50ml, following the method outlined by Abd El- Kader et al (2016). Determination of heavy metals in water samples were performed by atomic absorption spectrophotometer, according to the guidelines of A.O.A.C.…”
Section: Chemical Analysis Of Watermentioning
confidence: 99%
“…Initial digestion was conducted at room temperature for 4h, followed by heating at 40-45°C for 1h in a water bath and then raised to 70°C until the end of digestion. After cooling at room temperature, each digested sample was diluted to 60ml with deionized water and filtered out into a volumetric flask for analyzing heavy metals (Mahmoud & Abu Taleb, 2013;Abdel Kader et al, 2016).…”
Section: Determination Of Heavy Metalsmentioning
confidence: 99%